2018
DOI: 10.1002/ptr.6228
|View full text |Cite
|
Sign up to set email alerts
|

Aloysia citriodora Palau (lemon verbena) for insomnia patients: A randomized, double‐blind, placebo‐controlled clinical trial of efficacy and safety

Abstract: Aloysia citriodora (A. citriodora) has a long history of traditional use for sedation and treatment of insomnia in different societies. This study was carried out to assess the efficacy of A. citriodora in patients with insomnia. One hundred patients were randomly divided into two groups of A. citriodora (total essential oil 1.66 mg/10 ml and total amount of flavonoid in terms of quercetin 3.22 mg/10 ml of the syrup) and placebo. They were advised to use 10 cc of the syrups; an hour before the bedtime for a pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 37 publications
0
29
0
4
Order By: Relevance
“…Few studies have clinically demonstrated that lemon verbena can improve sleep quality and stress. For example, a clinical study in patients with insomnia reported improved perceived sleep quality after 4 weeks of lemon verbena intake [ 31 ]. In another study, lemon verbena extract reduced the number of awakenings during the night, and less reported anxiety after 3 weeks of intake in amateur athletes [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have clinically demonstrated that lemon verbena can improve sleep quality and stress. For example, a clinical study in patients with insomnia reported improved perceived sleep quality after 4 weeks of lemon verbena intake [ 31 ]. In another study, lemon verbena extract reduced the number of awakenings during the night, and less reported anxiety after 3 weeks of intake in amateur athletes [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Association of insomnia with chronic diseases, such as obesity, type 2 diabetes, cardiovascular disease, neurological issues including mood swings, increased mortality has been established as evidenced by available literature [5]. A survey suggests, more than 80% global population use plant extracts as medication for primary health care [6,7]. Ashwagandha found across India and south Asia, is a respected herb in traditional Indian Ayurveda, scientifically known as Withania somnifera (L.) Dunal.…”
Section: Introductionmentioning
confidence: 99%
“…Questionnaires were used at three intervals; at the baseline, 2 and 4 weeks after the enrollment. Data analysis showed that scores of global PSQI (measuring sleep latency, habitual sleep efficiency, daytime dysfunction, and subjective sleep quality) and ISI in the Aloysia citriodora group were higher after 2 and 4 weeks of treatment when compared with the placebo group [131].…”
Section: Migrainementioning
confidence: 93%